Ca2 + dynamics correlates with phenotype and function in primary human neutrophils - Hübner, Katrin; Surovtsova, Irina; Yserentant, Klaus; Hänsch, Gertrud Maria; Kummer, Ursula (Biophysical chemistry, 2013)
Central to the immune defense function of neutrophils is to sense, to move and to kill. Neutrophils acquire distinct cellular states necessary to fulfill these functions each associated with a particular phenotype. The cells constituting the neutrophil population are presumably not synchronized with respect to their actual state, e.g. due to maturity or preactivation. It is also likely that they exhibit a different degree of phenotypic plasticity (that is, the ability to switch to a particular state). Calcium is known to play a crucial role in neutrophils such as for cell motility. The present study focuses on characterizing the cell-to-cell variability at the morphological as well as at the level of calcium dynamics by studying single primary human neutrophils. We apply long-term multivariate live cell imaging to (i) characterize neutrophil phenotypes of different functional states, (ii) analyze the distribution of cells being in these states and, (iii) study the individual intracellular calcium response simultaneously with shape changes. We are able to differentiate the five distinct subpopulations of neutrophils based on quantitative parameters of cell morphology and motility. As a major result, we demonstrate that the calcium dynamics of individual cells correlates with their respective functional state. Finally, we see a number of cells that undergo spontaneous phenotypic changes from one cellular state to another. These events are preceded either by exhibiting the calcium dynamics of the future state or by switching to the respective calcium dynamics in parallel to switching the morphology. Based on our results we conclude that specific calcium dynamics carries crucial information for the function and phenotype of neutrophils.